Reflections on an Academic Leadership Approach to Implementing Digital Education in Higher Education - Gloria Visintini (MDPI AG, 2022)
The aim of this paper is to reflect upon personal experiences with a Foucauldian-inspired academic leadership approach to implementing digital education at the University of Bristol. Higher Education Institutions across the UK often invest in digital infrastructure and central support teams (technical and educational) and expect these investments alone to be the main vehicles to achieve digital education. While clearly, having technologies and support play a key role in digital education, according to my experience the implementation of digital education is complex and requires focused and scholarly leadership to drive it. This is because I argue that digital education can be considered a 'discourse', in the Foucauldian sense, of our era whose implementation involves considerable social change. Through my work as the academic person first responsible for digital education in the School of Modern Languages and then across the Faculty of Arts at the University of Bristol, I will unpack how having someone with the appropriate practical and theoretical expertise leading the digital education agenda brought positive impacts before and during the pandemic. Drawing on reflections from years of academic leadership, I will consider questions such as: What practices can lead the digital education discourse to advance in HE settings? And, which agents in HE can develop these practices? This theoretical-oriented discussion grounded on personal experience can be useful for institutions making decisions about how to take digital education forward. Indeed, as we emerge from the pandemic, universities are in the process of choosing whether to go back to a pre-COVID time characterised by a power struggle between different educational discourses, which often meant that the digital education discourse remained marginal, or whether to embrace and invest more in digital education and associated academic leadership.